2019
DOI: 10.1002/acr.23709
|View full text |Cite
|
Sign up to set email alerts
|

Time of Disease‐Modifying Antirheumatic Drug Start in Juvenile Idiopathic Arthritis and the Likelihood of a Drug‐Free Remission in Young Adulthood

Abstract: Early DMARD treatment is associated with better disease control and outcomes, which supports the concept of a 'window of opportunity' for JIA. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 39 publications
2
42
0
11
Order By: Relevance
“…35 An analysis of the BiKeR registry demonstrated that earlier treatment with a biological agent (within 2 years of symptom onset) was associated with better disease control and drug-free remission. 36 Taken together, these results suggest that early response to treatment is associated with disease remission in patients with JIA, and therapy adjustments are warranted early on in patients who fail to respond. Of note, RF negativity was not a predictor of achieving remission in our analysis, although RF-positive polyarticular JIA has been associated with lower rates of remission than other JIA forms in the past.…”
Section: Discussionmentioning
confidence: 79%
“…35 An analysis of the BiKeR registry demonstrated that earlier treatment with a biological agent (within 2 years of symptom onset) was associated with better disease control and drug-free remission. 36 Taken together, these results suggest that early response to treatment is associated with disease remission in patients with JIA, and therapy adjustments are warranted early on in patients who fail to respond. Of note, RF negativity was not a predictor of achieving remission in our analysis, although RF-positive polyarticular JIA has been associated with lower rates of remission than other JIA forms in the past.…”
Section: Discussionmentioning
confidence: 79%
“…In den vergangenen 2 Jahrzehnten haben sich die medikamentösen Optionen bei der Behandlung der juvenilen idiopathischen Arthritis deutlich erweitert. Das Erreichen von Entzündungsfreiheit und Remission sind ein realistisches und erreichbares Therapieziel geworden, womit sich Lebensqualität und Teilhabe von Kindern und Jugendlichen mit JIA deutlich verbessert haben [2,[20][21][22][23].…”
Section: Diskussionunclassified
“…Remission ist inzwischen das angestrebte Therapieziel und wird von der Mehrheit der Patienten (70-95 %) in den ersten Behandlungsjahren erreicht [3]. Die Änderungen im therapeutischen Vorgehen haben die Langzeitprognose der Patienten durch Abnahme von Folgeschäden und Funktionseinschränkungen im Alltag sukzessive verbessert [4]. Der therapeutische Fortschritt wurde von der Entwicklung und Validierung standardisierter Instrumente für die Bewertung des Therapieansprechens begleitet, wie z.…”
Section: Introductionunclassified
“…Das JIA-Biologika-Register JuMBO liefert außerdem wichtige Daten zur Versorgung [23], zum Verlauf und Outcome [24] der JIA im Erwachsenenalter. Bisher lagen keine Daten vor, ob der frühe Einsatz von bDMARDs Einfluss auf das Outcome der JIA im jungen Erwachsenenalter hat.…”
Section: Outcome Von Bdmard Behandelten Patienten Im Erwachsenenalterunclassified
“…Bisher lagen keine Daten vor, ob der frühe Einsatz von bDMARDs Einfluss auf das Outcome der JIA im jungen Erwachsenenalter hat. Diese Lücke konnte mit dem JuMBO-Register geschlossen werden [24]. Patienten mit einem bDMARD-Therapiebeginn innerhalb der ersten 2 Erkrankungsjahre erreichten signifikant häufiger nach 10 Jahren Erkrankungsdauer eine inaktive Erkrankung (28 % versus 18 %) oder auch eine medikamentenfreie Remission (18 % versus 5 %) im Vergleich zu Patienten, die erstmals nach mehr als 5 Jahren Erkrankungsdauer mit einem bDMARD behandelt wurden.…”
Section: Outcome Von Bdmard Behandelten Patienten Im Erwachsenenalterunclassified